ANALISIS PERANCANGAN ALAT BANTU KERJA OPERATOR ANGKUT DI STASIUN PEMANENAN PADA PT PERKEBUNAN X - Risky Hidayat; Listiani Nurul Huda; Poerwanto M.Sc (Jurnal Teknik Industri USU, 2013)
PT Plantation X is a company engaged in oil palm and rubber plantations. The study focused on the problems of transporting TBS (fresh fruit bunches) of oil palm using rickshaw. Rickshaw used to transport the the yields which harvested by dodos started from citing TBS using gancu and scattering berondolan cited by hand then to put it in a small bucket. TBS and berondolan transported by rickshaw then poured into TPH (The calculation results) to be weighed. The transport work process done with not ergonomically that potentially cause musculoskeletal complaints (MSDs). Methods that used in data collection and problem solving, which are SNQ, REBA, and anthropometric approaches. SNQ (standard Nordic questionnaire) used to know MSDs worker complaints. REBA method is used to see the level of risk based on the work position. Anthropometric data are used to guide the design of a rickshaw in accordance with the workers posture. Results showed snq complaint occurred in the shoulder, waist, thighs and on the right side of the body. Complete review using REBA on elements of activities demonstrate the needs to improve the transport facilities, especially the rickshaw which is a facility that is always used by the transport workers. Anthropometric data which used in redesign the work tool for transport operators are shoulders height, arm reach, shoulders width, and hands.